New extra-Amazonian records of the Black-billed Cuckoo Coccyzus erythropthalmus (Cuculidae) for Brazil (Avocetta, 2024)
The breeding grounds of the Black-billed Cuckoo Coccyzus erythropthalmus encompass a wide area in northern North America. During the austral winter individuals migrate to non-breeding areas in South America. There had been only three known locations for the species in Brazil, two in the Amazon Forest and one in the Atlantic Forest. Here, we aim to present new records in Brazil and to organize the available literature recovering historical data. The new records are in the Southeast and South regions and thus represent the first documented records outside the Brazilian Amazon. These findings indicate an expansion of the area considered nomadic for the species. All extra-Amazonian records were made in strong El Niño years, a climate phenomenon that may be changing bird migration patterns in South America, which requires further investigation.
Keywords: Animal movement; Atlantic Forest; Conservation; Vagrant bird; Serra do Mar; Natural history; El Niño; Migration